Pengaruh Kepemimpinan Transformasional dan Kepuasan Kerja dengan Motivasi Kerja sebagai Variabel Moderating terhadap Kinerja Karyawan pada PT Mandiri Utama Finance - Ulfa Yulyani; Saban Echdar; Deddy Rahwandi (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2021)
This study aims to determine and analyze: the effect of transformational leadership and job satisfaction with work motivation as an intervening variable on employee performance at PT Mandiri Utama Finance employees. This research approach uses quantitative research. The research was conducted at PT Mandiri Utama Finance. The time of the study began in July 2020. The study population was all employees of PT Mandiri Utama Finance, amounting 180 peoples. The sample selection in this study was carried out using purposive sampling method, namely sampling with certain criteria. Where the criteria for respondents specified in this study are respondents who are currently working at PT. Mandiri Utama Finance with the status of a permanent employee. Because this study focuses on leadership, so the sample in this study selects employees who have junior. So that the sample in this study amounted to 68 people. The results of this study indicate that: 1) There was an effect of transformational leadership on employee performance, 2) There was an effect of job satisfaction on employee performance, 3) There was an effect of transformational leadership on work motivation, 4) There was an effect of job satisfaction on work motivation, 5) There was an influence work motivation on employee performance, 6) There was an effect of transformational leadership on employee performance through work motivation, and 7) There was an effect of job satisfaction on employee performance through work motivation. The importance of transformational leadership, job satisfaction and work motivation because it can affect the performance level of an employee.